A new and fast continuous method for the pre-treatment of dehydrated broth for total creatinine determination - Acebal, Carolina Cecilia (2005)
The quantification of total creatinine contributes to the quality control in meat products. The reference method for dehydrated broths treatment is tedious and takes approximately 6 h. A fast, simple and relatively safe procedure to the pre-treatment of these samples was developed by using a focussed microwave oven which works in continuous way. The optimization of the different variables for the pre-treatment was made and the validation of the method was carried out in order to ensure the accuracy of the obtained results.